Misbehavior detection of nodes in mobile ad-hoc networks using cluster overheads - Purnasai, Rampati; Suryakala, Vasanthadev; T, Ramya; S, Kolangiammal (International Journal of Engineering and Technology, 2018)
In this paper we mainly discuss about the problem of identifying the misbehaving nodes in a multi hop ad-hoc network. Misbehaving nodes identification is done using co-operative incentive based approaches. We are considering a cluster based system for identifying misbehaving nodes in a network. A cluster overhead is selected in each cluster for communicating with other clusters. Proposed system is capable of detecting misbehaving nodes using the cluster formation and also the degradation of network lifetime is decreased when compared to the existing protocol. By selecting the cluster over-head we have marginally reduced the time-delay and packet loss ratio in (network simulator 2) simulation environment. Acknowledgement schemes are used to identify selective packet droppers.